Impact of Peanut Ball Device on the Duration of Active Labor: A Randomized Control Trial - Mercier, Rebecca J.; Kwan, Mei (American Journal of Perinatology, 2018)
Objective To evaluate whether the use of a peanut ball device shortens the duration of active labor in nulliparas.Study Design Single-site, nonblinded randomized trial in nulliparous women admitted for labor or labor induction. English-speaking women > 18 years of age with singleton pregnancies were enrolled. Participants were randomized to the use of peanut ball or usual care upon reaching the active phase of labor (≥ 6 cm cervical dilation) with an epidural. Primary outcome was rate of cervical dilation. Secondary outcomes were rates of cesarean delivery and fetal presentation at time of full dilation or delivery.Results Ninety-six patients enrolled; 63 reached full cervical dilation. There was no statistically significant difference in rates of cervical dilation (0.98cm/h vs. 0.79cm/h, p = 0.27) or length of labor (315 minutes vs. 387 minutes, p = 0.14) between the groups. There was no difference in the rates of cesarean delivery (33% vs. 35%, p = 0.8) or occiput posterior presentation. (28% vs. 9%, p = 0.09). Among the subgroup who had labor arrest, fewer patients using the peanut ball experienced arrest of dilation; this approached but did not reach statistical significance (30% vs. 73% p = 0.05).Conclusion Use of the peanut ball does not significantly increase rates of cervical dilation or decrease time in active labor.
Keywords: active labor; dystocia; epidural; cesarean delivery; fetal malposition; birthing ball